Does financial crisis impact earnings management evidence from Portuguese and UK - Lisboa, Inês (2018)
Purpose: The main aim of this work is to analyse if 2008 financial crisis had impact on earnings management. We compare two countries with different legal forces in terms of quality of accounting to see the differences in firm’s involvement in earnings management. Finally we analyse which determinants impact management of results. Design/methodology/approach: This study focus on Portuguese and UK listed firms from a large period, 2004 till 2014. We first use the Kothari, Leone & Wasley model (2005) to calculate the discretionary accruals, a proxy of earnings management. Then we analyse the impact of six determinants on earnings management. Findings: Findings suggest that financial crisis had impact on firms’ tendency to manage financial results. Country effect is not statistically significant, even if the Portuguese and UK firms’ propensity to manage earnings is singular. Finally, firm’s size and indebt are two relevant characteristics to explain earnings management. Originality/values: This research as three major contributions. First, we not only analyse if the firms in the sample manipulate results, but we also study the impact of some characteristics on earnings management, contributing to the enrichment of the literature. Moreover, we focus on two main effects: crisis and country effect. Studies analysing both effects in simultaneous are scarce. Finally, we also believe that results are relevant to both financial investors and regulators as they may understand which factors impact manipulation of results, and can take actions that may reduce the possibility of practicing earnings management.